The Effectiveness of Solution Focused Brief Counseling (SFBC) Based on Creative Art to Reduce Students Social Aggressive Behaviour - Putri, Dhia Adinda; Saputra, Wahyu Nanda Eka; Hartanto, Dody; Nugraha, Ariadi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2019)
The current study aimed to investigate the effectiveness of SFBC to decrease social agresive behaviour among the students of 12th grade in SMA Muhammadiyah 1 Prambanan. This study was an experiment study and used pre-experimental design employing one group pretest posttest model. The subject of this current study was students of 12th in SMA Muhammdiyah 1 Prambanan. In determining the subject, the researcher used nonprobablility sampling design with purposive sampling. The finding found a significant difference between students' social agresive level before and after they were treated with SFBC based on creative arts.